2019
DOI: 10.21082/fae.v36n1.2018.45-61
|View full text |Cite
|
Sign up to set email alerts
|

Dinamika Kelembagaan Kemitraan Usaha Rantai Pasok Buah Tropika Berorientasi Ekspor

Abstract: <p>The main problem faced in the development of Indonesia's tropical fruits are the lack of variety, quantity, quality and continuity of supply that is in line with market demand dynamics and consumer preferences. The purpose of this paper is to examine the performance of export-oriented tropical fruit business partnership institutions. The method of analysis is carried out by reviewing various literature studies, especially primary scientific journals and other data and information. Indonesia's main tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Mereka bahkan memperoleh informasi ini dari petani dan pedagang besar lain yang merupakan mitra bisnis. Informasi adalah input utama dalam sistem pengambilan keputusan (Perwita., Darwis & Suhartini., 2019). Karena jarak antara petani dan pedagang besar di Kota Bau-Bau 116 km, sehingga transportasi pengangkutan rumput laut menggunakan mobil pickup, yang biayanya Rp.1000 per/kg.…”
Section: Pedagang Besarunclassified
See 1 more Smart Citation
“…Mereka bahkan memperoleh informasi ini dari petani dan pedagang besar lain yang merupakan mitra bisnis. Informasi adalah input utama dalam sistem pengambilan keputusan (Perwita., Darwis & Suhartini., 2019). Karena jarak antara petani dan pedagang besar di Kota Bau-Bau 116 km, sehingga transportasi pengangkutan rumput laut menggunakan mobil pickup, yang biayanya Rp.1000 per/kg.…”
Section: Pedagang Besarunclassified
“…Pada hasil penelitian Masela & Lusnarnera (2022) juga menjelaskan bahwa karena sudah ada keterkaitan antara petani rumput laut dan pedagang pengumpul, petani dapat memperoleh informasi tentang harga rumput laut dari pedagang yang sudah menjadi pelanggannya. Informasi adalah input utama dalam sistem pengambilan keputusan (Perwita., Darwis & Suhartini., 2019).…”
Section: Pola Kemitraan Patron Klienunclassified
“…The results of the study revealed that imported oranges are still superior to local oranges, especially in terms of quality, however, keprok tangerines can relatively compete with imported oranges [12]. Quality is everything that shows a product's specialty or degree of superiority, in this case, citrus fruit products [13]. The results of research on the melon supply chain in Karanganyar district stated that product quality was the main factor in establishing efficient supply chain management [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, discriminative institutions burden small farmers, making the farmers unable to access agricultural inputs, inter alia, fertilizer and seeds. Lastly, the supply chain in the agricultural trade system is another thread confronted by farmers as the margin of the farm is determined by how effectively the supply chain works [12][13] Sectoral inequality topics are increasingly popular in recent times. Inequality is often measured from the difference in income per capita based on regional boundaries, such as using the Gini index and the Williamson index.…”
Section: Introduction 1backgroundmentioning
confidence: 99%